Optimal linear control applied to vibro-impact structures (Research, Society and Development, 2020)
Many mechanical equipment, when performing their functions, generate some type of noise. These noises can be mechanical vibrations, represented by speeds, accelerations and displacements. In most structures, these vibrations are considered unwanted. However, it is worth mentioning that, in some applications, they are necessary to maintain the proper functioning of machines and equipment, such as impact drills and compressor rollers. In order to represent experimental physical models numerically, it is common to use computer software that simulates their dynamic behavior. This helps to predict project failures and prevent accidents, saving time and, consequently, money. In this work, an analysis of the dynamic behavior of a system under impact suppression was performed. The variation parameter used was the excitation frequency, and according to the studied parameters, a chaotic behavior of the structure was noted. Therefore, in order to mitigate this chaotic behavior, an optimal linear control project (LQR) was developed, and its implementation was presented efficiently, reducing the amplitude of the response parameters, and minimizing the chaotic trajectories of the structure.